Hydrogen production by methane decomposition over Ni-doped activated carbons: effect of the activation method - Mahmoudi, Marwa; Dufour, Anthony; Bettahar, Mohammed El-Miloud; Medjahdi, Ghouti; Ouederni, Abdelmottaleb; Gadiou, Roger (Comptes Rendus. Chimie)
Ni supported over activated carbon (AC) based on olive stones were tested for methane decomposition to produce hydrogen. Physical (by $H_{2}O$) and chemical (by $H_{3}PO_{4}$) activations were compared. Kinetic parameters of methane decomposition were determined depending on Ni load, methane partial pressure and reaction temperature. The catalysts were characterized before and after reaction by $N_{2}$ adsorption, X-ray Diffraction (XRD) and Transmission Electron Microscopy (TEM). The catalysts showed good initial activities that increased with temperature and nickel load, reactivity decreased with time. The reaction orders were 0.63 and 0.74 and the activation energies were 122 and 139 kJ/mol for physically and chemically activated carbon, respectively. BET surface areas and pore volumes decreased dramatically after reaction due to the deposit of carbon on the support. Ni stayed under its metallic form on the physically AC whereas it was mainly present as $Ni_{12}P_{5}$ over the chemically activated one. TEM characterization revealed the formation of well-organized carbon nano-onions surrounding Ni particles on the physically activated carbon. Nano-onions were not formed around $Ni_{12}P_{5}$ particles in the chemically activated carbon. The physical activation allowed the synthesis of catalysts with a better stability for methane conversion than what chemical activation would allow.